Tethered Signaling in Inhibitory Immune Receptors - Pérez-Ferreros, Pablo; Gaus, Katharina; Goyette, Jesse (Frontiers in Physics, 2019)
Leukocytes play critical roles in preventing pathogenic infection and controlling transformed cells, but must remain quiescent in response to healthy tissue. To execute this function, immune cells need to integrate signals from a host of activatory, co-activatory, and co-inhibitory immune receptors. When an immune cell interacts with another cell containing ligands for these receptors, an immunological synapse is formed at the contact interface that acts as a dynamic signaling hub into which cytoplasmic enzymes are recruited and tethered. Within this interface competing tethered enzymatic activities are integrated, ultimately leading to the cellular decision to respond or remain quiescent. Here, we review recent advances in our understanding of tethered signaling reactions, focusing on proximal signaling downstream of important T cell immune receptors. We discuss how a class of co-inhibitory receptors require co-localization with activatory receptors to function, how recent evidence that T cells use microvilli to probe antigen presenting cell surfaces may be important for immune receptor function, and how co-clustering between activatory and inhibitory receptors facilitates integration of tethered reactions.